2008
DOI: 10.1055/s-0028-1088388
|View full text |Cite
|
Sign up to set email alerts
|

Vasodilator and Antioxidant Effect of Xanthones Isolated from Brazilian Medicinal Plants

Abstract: Vasorelaxant and antioxidant activities are important in the therapy for cardiovascular diseases. We aimed at investigating the vasorelaxant and antioxidant activities of six xanthones isolated from Brazilian medicinal plants. Xanthone ( 1), 1-hydroxyxanthone ( 2), 4-hydroxyxanthone ( 3), 1-hydroxy-8-methoxyxanthone ( 4), 1,3-dihydroxy-7-methoxyxanthone ( 5) and 2,6,8-trihydroxy-1-methoxyxanthone ( 6) induced concentration-dependent vasorelaxant effects in endothelium-intact mice aortic rings. The presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…Hydroxyxanthones are abundantly found in many plants [ 16 , 17 ] and are reported to have a great deal of biological activities including vasorelaxing, antimalarial and antioxidative effects [ 18 , 19 ]. In particular, being a rich source of natural hydroxyxanthones, mangosteen (Garcinia mangostana) has long been used to treat diarrheal illness in traditional medicine, and more recently is considered a natural chemopreventive agent [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Hydroxyxanthones are abundantly found in many plants [ 16 , 17 ] and are reported to have a great deal of biological activities including vasorelaxing, antimalarial and antioxidative effects [ 18 , 19 ]. In particular, being a rich source of natural hydroxyxanthones, mangosteen (Garcinia mangostana) has long been used to treat diarrheal illness in traditional medicine, and more recently is considered a natural chemopreventive agent [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Xanthones have been reported to have numerous biological properties, including the antithrombotic and anticancer effects, 5 protein kinase C inhibitor activity, 6 antihypertensive and vasodilatory effects, 7 endothelial cell protective effects, 8 anti-inflammatory, 3,5,[9][10][11] analgesic, 10 and antioxidant activities. 4,7 The 2,8-dihydroxy-1,6-dimethoxyxanthone has been isolated from the H. paniculata, 12 Triperospermum chinense, 13 Gentiana kochiana, 14 and Juglans mandshurica 15 genera. This xanthone has been described as an antimycobacterial agent 16 and elicits central inhibition of monoamine oxidase A.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, structure-activity analysis of plant-derived flavonoids has suggested that phenolic groups are responsible for the inhibitory effect of flavonoids on cAMP-activated Cl − secretion (Illek et al, 2000). Hydroxyxanthones are phenolcontaining molecules abundantly found in many plants, especially those of Clusiaceae or Guttiferae, and are reported to have a great deal of biological activities including vasorelaxing, antimalarial and antioxidative effects (Capettini et al, 2009;Ignatushchenko et al, 1997;Wang et al, 2008). In particular, mangosteen (Garcinia mangostana), which is a rich source of natural hydroxyxanthones, has long been used to treat diarrheal illness in traditional medicine (Pedraza-Chaverri et al, 2008).…”
Section: Introductionmentioning
confidence: 99%